PENGARUH KEBERAGAMAN GENDER DEWAN DIREKSI DAN STRUKTUR KEPEMILIKAN TERHADAP FINANCIAL DISTRESS - Puspasari, Oktaviani Rita; Nurhandika, Arief; Fitriani, Chintia (Jurnal Riset Keuangan dan Akuntansi, 2024)
This research aims to examine and analyze the effect of board gender diversity and ownership structure on financial distress. Board gender diversity shows the portion of women on the board of directors and the ownership structure includes managerial ownership, institutional ownership, and public ownership. The population was a transportation service company listed on The Indonesian Stock Exchange from 2016 to 2021. The sampling technique used purposive sampling with a sample of 52 companies for six years or 312 observations. Then, hypothesis testing employed logistic regression analysis. The results of the study indicated that the managerial ownership structure and gender diversity on the board have a small but unfavourable impact on financial distress.  Financial distress is significantly impacted negatively by both public and institutional ownership structures. This research presents empirical support for agency theory and reviews the literature on the function of corporate governance practises in foretelling financial trouble in businesses in the transportation sector. This research presents empirical support for agency theory and reviews the literature on the function of corporate governance practises in foretelling financial trouble in businesses in the transportation sector. Keywords: board gender diversity, managerial ownership structure, institutional ownership structure, public ownership structure, financial distress